Pengaruh Digital Marketing dan Brand Image Terhadap Keputusan Pembelian dan Loyalitas Pelanggan: studi kasus pada produk fesyen - Itriatus Zakia; Bambang Setiyo Pambudi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study examines how brand image functions as a mediator in the interaction between digital marketing and its impact on customer loyalty and purchasing decisions. This study focuses on students at the University of East Java (83.5% undergraduate students) who purchase fashion products from Generation Z, a very important group in the digital era. This study distributed questionnaires to 100 respondents as part of its quantitative research methodology. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 was used to analyze the research data. The results show that Brand Image (Z) (p=0.000), Purchase Decision (Y1) (p=0.000), and Customer Loyalty (Y2) (p=0.036) are all positively and statistically significantly influenced by Digital Marketing (X). These results prove the importance of digital marketing tactics in shaping the attitudes and actions of Generation Z consumers. According to statistical analysis, digital marketing (X) has a positive and significant impact on Purchase Decision (Y1) (p=0.000) and Customer Loyalty (Y2) (p=0.036), demonstrating the effectiveness of digital marketing strategies in directly influencing Gen Z consumers in East Java. Additionally, it has been proven that digital marketing is a strong factor in developing Brand Image (Z) (p=0.000). Based on the study findings, brand image has a different impact on these two dependent variables. Customer Loyalty (Y2) was found to have a positive and statistically significant impact on Brand Image (Z) (p=0.000). On the other hand, it was found that Brand Image (Z) has a favorable but insignificant impact on Purchase Decision (Y1) (p=0.199). This study suggests that Generation Z may be more influenced by transactional variables (such as digital promotions) than long-term brand image perceptions when making immediate purchases.